Ada Lamarr’s Character Development in Beth Revis’s Full Speed to a Crash Landing - Nuristama, Ramadhina Ulfa; Sa'adah, Sufi Ikrima; Hikmawati, Masna (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article aims to examine the character development of the main character, Ada Lamarr, in Full Speed to a Crash Landing by Beth Revis. The focus of this study is on the changes in the characteristics of the main character, which are identified in the attitudes, behaviors, and traits of the main character. This study uses a qualitative research method. The New Criticism theory is applied to examine the characters, characterizations, and character development. Data were taken from the novel through a close reading process, then identifying the initial and final characteristics of Ada Lamarr depicted in the novel. The collected data are analyzed using the theory, and a conclusion is made. The results of the analysis show that Ada Lamarr experienced changes in her characteristics on her journey to complete her space mission. Initially, Ada is depicted as a tough and independent figure. Still, realizing the many dangers and obstacles in completing her mission, Ada becomes more tolerant and cooperates with others. This is inseparable from her mission, which is very close to danger. This character development certainly helps strengthen the theme in the novel that, in completing a dangerous mission, the main character must adapt to other characters so that the mission can be accomplished.